Sector Unit-Cell Methodology for the Design of Sub-6 GHz 5G MIMO Antennas - Jaime Molins-Benlliure; Marta Cabedo-Fabres; Eva Antonino-Daviu; Miguel Ferrando-Bataller (IEEE Access, 2022)
A novel methodology based on the sectorization of multiple-port cavities with azimuthal symmetry into sector unit cells is presented to design 5G multiple-input multiple-output (MIMO) sub-6 GHz antennas. The methodology divides an N-port cavity antenna into N unit cells and predicts the performance of the N-port design with the analysis of two adjacent cells. This approximation reduces the time and complexity of the simulation of cavity antennas with a high number of ports. For the theoretical justification, cavity mode analysis of a closed cavity and characteristic modes analysis of open and sector cavities is addressed. With the use of the proposed methodology, five different cavity designs with circular, square, hexagonal, octagonal, and saw-tooth geometries are presented in this article. In addition, the fabrication of the 4-port circular shape design and its MIMO performance is also studied. Results show an impedance bandwidth of 130% (1.27-6 GHz), and an envelope correlation coefficient (ECC) lower than 0.1.